2020
DOI: 10.1590/2177-6709.25.5.057-065.bbo
|View full text |Cite
|
Sign up to set email alerts
|

Importance of orthodontic intervention of the Class III malocclusion in mixed dentition

Abstract: Introduction: Supervising the development of occlusion, managing problems during the transition from mixed to permanent dentition, as well as controlling environmental factors that contribute to establishing malocclusion, are important actions to achieve a Class I occlusion with facial balance. Among these problems, the malocclusions associated with dysfunctions such as mouth breathing or obstructive sleep apnea syndrome (OSAS), atypical swallowing and abnormal tongue position, open bites, crossbites and maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
(51 reference statements)
0
3
0
2
Order By: Relevance
“…Por ende. Brito y col en el 2015 indican que el desarrollo de las desarmonías oclusales y esqueléticas pueden comenzar a edades tempranas; por lo que, el tratamiento temprano es definitivamente una posibilidad viable, ya que existen variables favorables tales como: el crecimiento, desarrollo y maduración, el patrón de crecimiento esquelético, entre otros; por lo tanto, podría ser posible cumplir con los objetivos de un tratamiento ortopédico que corrija el crecimiento desfavorable, a su vez, previniendo la desarmonía dental, esquelética y por consiguiente la mejora de la oclusión estética, estática y dinámica (21).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Por ende. Brito y col en el 2015 indican que el desarrollo de las desarmonías oclusales y esqueléticas pueden comenzar a edades tempranas; por lo que, el tratamiento temprano es definitivamente una posibilidad viable, ya que existen variables favorables tales como: el crecimiento, desarrollo y maduración, el patrón de crecimiento esquelético, entre otros; por lo tanto, podría ser posible cumplir con los objetivos de un tratamiento ortopédico que corrija el crecimiento desfavorable, a su vez, previniendo la desarmonía dental, esquelética y por consiguiente la mejora de la oclusión estética, estática y dinámica (21).…”
Section: Discussionunclassified
“…En contexto de las maloclusiones clase III, se estima que cuentan con uno de los tratamientos más complejos de ortodoncia, por contener diferentes combinaciones tanto de patrones dentales como esqueléticos anormales y caracterizados por presentar: retrognatismo maxilar, prognatismo mandibular o una combinación de ambos (19). En cuanto a la etiología se considera que podría ser de tipo multifactorial, con afecciones tales como: amígdalas hipertróficas, interferencias oclusales, erupción irregular de los incisivos permanentes, pérdida prematura de molares deciduos o agenesia de dientes maxilares, que podrían estar relacionadas con la hipoplasia maxilar; así también, la presencia de dientes supernumerarios mandibulares que provocan un aumento del tamaño del arco mandibular, hábitos como la protrusión lingual y no obstante la herencia, que desempeña un papel importante en el desarrollo de ésta maloclusión, de manera que, al saber identificar el factor causante, este determinará el diagnóstico y pronóstico para poder interceptar tempranamente la maloclusión (principalmente durante la fase de dentición mixta) ya que la Clase III tiende a expresarse durante el crecimiento y mientras más pronto inicie el tratamiento mayores serán los efectos ortopédicos, evitando así en un gran porcentaje la cirugía ortognática al final del crecimiento (20,21).…”
Section: Figura 2 Porcentaje De Los Tipos De Estudios De Los Artículo...unclassified
“…The FRII functional appliance is used to maintain the median relationship to the IIIA stage, provide a good environment for the normal development of the jawbones, guide the normal growth of the jawbones, and improve the facial shape. This approach alleviates the concerns of children and their families to a certain extent and increases confidence in the therapeutic effect [ 29 ].There was no recurrence during the study period, indicating that this method can provide a new method and idea for the correction of skeletal class III malocclusion. However, for children with skeletal Class III malocclusion, it should be observed until the early adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] It was reported that early treatment with a facemask appliance has a positive impact on both dental and skeletal parameters, and reduces the need for orthognathic surgery in the future when treatment is performed before the age of 10 years in mild to moderate Class III with a retrusive maxilla and no hyperdivergent facial growth pattern. [34][35][36][37][38][39][40][41][42][43] Baccetti et al 44,45 demonstrated that, especially in the pure deciduous dentition at age 5 years, treatment produces more beneficial skeletal effects such as significantly smaller increments in mandibular total length (Co-Pg) compared to more maxillary dentoalveolar protrusion when treatment is performed in the mixed dentition (around 8 years of age).…”
Section: Class III Malocclusionmentioning
confidence: 99%